The CXCR3/PLC/IP3-IP3R axis is responsible for the ignition of UPR in intestinal epithelial cells exposed to gliadin peptide, during the onset of celiac disease - Romina Monzani; Mara Gagliardi; Valentina Saverio; Nausicaa Clemente; Alice Monzani; Ivana Rabbone; Francesca Nigrelli; Samuele Pellizzaro; Emanuele Ferrario; Silvia Saettone; Nico Pagano; Luigina De Leo; et al. (Biology Direct)
Abstract Background Coeliac disease is an autoimmune disease that is primarily associated with chronic inflammation of the gut, but can also affect organs outside the gut, from the liver to the skin and CNS. The disease is triggered in predisposed individuals by a peptide mixture (PT) derived from the digestion of gliadin, a component of wheat, which is ingested with food. Although the induction of endoplasmic reticulum stress in intestinal epithelial cells (IECs) upon exposure to PT is known, the underlying molecular mechanisms remain unclear. Identifying the key players in this signaling pathway could therefore help to develop a new effective therapeutic strategy for the treatment of CD patients. Methods Two CD models were used to identify the molecular mechanism linking extracellular PT and endoplasmic reticulum (ER) stress in the IECs of predisposed individuals exposed to gliadin. These models were an in vitro model based on CaCo-2 cells and an ex vivo model based on our previously described gut ex vivo system (GEVS), both exposed to PT. Results Our results clearly show that the interaction of gliadin peptides with the transmembrane CXCR3 receptor on IECs leads to a rapid induction of PLC activity that generates IP3 molecules. This second messenger binds to the IP3R located in ER membranes, resulting in calcium efflux from the organelle. Conclusion The PT-dependent ER stress observed in the IECs of CD patients results from the excessive release of calcium from the ER. Importantly, inhibition of this signaling pathway abrogates ER stress, which in turn attenuates downstream signs of CD, such as TG2 expression and gut permeability dysregulation, as well as inhibits inflammation.